Pelatihan Terapi Autis Metode Applied Behavior Analysis (ABA) (Studi Kasus Pada Proses Pelatihan Terapi Autis Di Lembaga Pemasyarakatan Kelas 1 Tangerang - Julimet, Nofri; Cholid, Sofyan (UI Scholars Hub, 2015)
Applied behavior analysis was a method of healing autistic that have not known by the Indonesian. Meanwhile, ABA was effective and efficient in reducing the behavior of disruptive which shown in autistic. Then, the benefit of ABA was taught in a systematic, structured, and measurable. This the-sis descrubed the training process of autism therapy that carried out in prison class 1 Tangerang, the instructor was inmates X. This research used qualitative approach by using depth-interview to the informants that consist of instructor, prison officers, and trainee. The is training including the three steps. Those were pre training, whils training, and post training, the most interesting activity was post training, that is doing a comparative study to the clinic ABA, practice and written exam. Although the training has ended the monitoring still done by the instructor.